Impact of Early versus Late Referral to Nephrologists on Outcomes of Chronic Kidney Disease Patients in Northern India. (1st June 2022) - Dhanorkar, Manoj; Prasad, Narayan; Kushwaha, Ravi; Behera, Manas; Bhaduaria, Dharmendra; Yaccha, Monika; Patel, Manas; Kaul, Anupama
Abstract : Background . CKD patients are often asymptomatic in the early stages and referred late to nephrologists. Late referred patients carry a poor prognosis. There is a lack of data on outcomes associated with referral patterns in CKD patients from northern India. Methods . In this observational cohort study, all CKD patients who visited the nephrology OPD of the institute between Nov 1, 2018, and Dec 31, 2020, were classified as early referral (ER) if their first encounter with a nephrologist occurred more than one year before initiation of dialysis and education about dialysis (from a nurse or nephrologist). The remaining others were considered late referrals (LRs). The outcomes impact of early and late referrals was analyzed. Results . A total of 992 (male 656) CKD patients (ER, n  = 475 and LR, n  = 517) were enrolled. Patients referred early were older and diabetic and had higher BMI, better education, occupation, and socioeconomic status as compared to those referred late. The mean eGFR at first contact with the nephrologist was (25.4 ± 11.5 ml/min) in ER and 9.6 ± 5.7 ml/min in the LR group and had a higher comorbidity score. The CKD-MBD parameters, hemoglobin, and nutritional parameters were worse in LR. Only a few patients had AVF, and the majority required emergency dialysis in the LR group. A total of 91 (9.2%) patients died, 17 (1.7% ER and 74 (7.5%) patients in the LR group patients. There was significantly lower survival at 6 months (ER 97.1% vs. LR 89.7%), 12 months (ER 96.4% vs. LR 85.7%), 18 months (ER 96.4% vs. LR 85.7%), and 24 months (ER 96.4% vs. LR 85.7%) in late referral group as compared to early referral group P = 0.005 . Conclusions . LR to nephrologists has the risk of the emergency start of dialysis with temporary vascular access and had a higher risk of mortality. The timely referral to the nephrologist in the predialysis stage is associated with better survival and reduced mortality.